Protection Of The Constitutional Rights Of Indonesian Women Workers In Malaysia - Riyanto, Slamet; Sumardi,; Firdaus, Yusuf; Sumerhu, Herru; Felina (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The purpose of this research is to determine the protection and constitutional rights of Indonesian workers, namely female workers abroad. The research method uses a qualitative approach to describe actual phenomena in the field. Data collection techniques using primary legal materials, secondary legal materials, and tertiary legal materials. Conclusion: TKI can generate foreign exchange of more than 20 (twenty) trillion rupiah. It is very clear that Indonesian migrant workers, especially Indonesian migrant workers, have contributed quite a bit of foreign exchange to the country. The Government's implementation of the protection of the constitutional rights of Indonesian migrant workers abroad is very weak and seems half-hearted. The concept of protection and implementation of protection for migrant workers abroad is made in the form of applicable laws and international agreements. The implementation of laws and regulations regarding the protection of Indonesian migrant workers and international agreements that aim to protect human rights and constitutional rights as citizens of Indonesian migrant workers who work abroad actually shows the weakness of the state in the eyes of the world in protecting their dignity and dignity.